'Seeing' Papua New Guinea: Making Order and Disorder through a Petroleum Project. Issue 1 (1st March 2019) - Dalsgaard, Steffen
Abstract : This article contributes to debates about how capitalist corporations 'see', and how they concurrently relate to the places where they are located. It argues that an analytical focus on 'seeing' illuminates how internal organization and outward relation making are tied together in complex ways. Even so, corporations of the extractive industries in particular cannot be assumed to encompass a single coherent view. The empirical case is a critical examination of how a gas project employed strict health, safety, and security measures to generate order when encountering alterity in an unfamiliar environment in Papua New Guinea. It reveals how the project was organized around two conflicting ways of seeing its host country—trying to separate itself from it while simultaneously having to engage and provide benefits for it.